Supercapacitors: Conductive Metal–Organic Framework Nanowire Array Electrodes for High‐Performance Solid‐State Supercapacitors (Adv. Funct. Mater. 27/2017). (17th July 2017) - Li, Wen‐Hua; Ding, Kui; Tian, Han‐Rui; Yao, Ming‐Shui; Nath, Bhaskar; Deng, Wei‐Hua; Wang, Yaobing; Xu, Gang
Abstract : In article number1702067, Yaobing Wang, Gang Xu, and co‐workers uniformly grow numerous nanowires of conductive metal‐organic framework (MOF) on carbon fibre paper, which can be directly used as the electrode in supercapacitors. A symmetric solid‐state supercapacitor composed of two identical electrodes and one separator is shown in the image. The material achieves the highest aerial capacitance and best rate performance reported yet for MOFs.